Third generation civil-military relations and the 'new revolution in military affairs' - Frederik Rosén (Danish Institute for International Studies (DIIS), 2009)
The encounter with insurgency violence in Iraq and Afghanistan has pressed the US Department of Defense to improve the US military's ability to conduct counterinsurgency. It has been argued that this shift may constitute a turning point in the history of the US military, which until now has focused its attention and resources on conventional warfare. The analysis is that the US military is currently in the process of 'learning counterinsurgency', but that it is still unclear whether this process will make counterinsurgency a US military priority. This working paper contributes to this discussion by looking at a particular aspect of the ambitious stabilization work that the US Department of Defense has commenced in Afghanistan, in which the US mili-tary is carrying out holistic civil governance reform projects. Whether such work will become a part of the US military's standard repertoire depends on the degree of success and possible entrenchment of the current innovations. However, as will be argued, this expansion of the functions of the military organization into civil governance is historical, and it might bring about pro-found changes to the US military, perhaps even transforming the notion of military more generally.
Keywords: 330; Militär; Gesellschaft; Afghanistan; Dänemark; USA